MODERN STATE AND PROGNOSIS OF DEVELOPMENT FOR WORLD TITANIC INDUSTRY ON PERIOD TO 2026: Report 4. Ferrotitanium - Kolobov, Herman; Panova, Vera; Nesterenko, Tetiana; Kirichenko, Aleksej; Rumyantsev, Vladislav; Volyar, Roman (Scientific Journal "Metallurgy", 2021)
The current state of ferrotitanium production capacities is described by producing countriesas both the largest such as Great Britain, Russian Federation and China and less powerfulones as Estonia, USA, Ukraine. The largest companies of these countries are indicated (TivacAlloys, AMG Superalloys UK, Mottram, AMG Superalloys UK, VSMPO-AVISMA, MidUral Group,Globe Titanium, Mast Europe) with their production technologies and ferrotitanium grades. Therequirements of consumers for different grades of ferrotitanium are analyzed. Markets and consumptionvolumes of titanium-containing products obtained using ferrotitanium (titaniumcontainingultra-low-carbon, high-strength low- and high-alloyed, stainless steels, superalloys)are indicated. The situation with international trade in ferrotitanium is considered; the main exportersand importers are indicated, as well as the volumes and directions of exports and imports.The share of ferrotitanium re-exports through the Netherlands and Estonia is also takeninto account. The dynamics of the price level for ferrotitanium since 2005 has been analyzed,with an indication of the reasons influencing the pricing. A forecast up to 2026 is presented interms of demand for ferrotitanium by application and price level. According to forecasts, by 2026ferrotitanium consumption will remain at the level of about 85 thousand tons per year. It is expectedthat the ferrotitanium market will continue to be provided with cheap raw materials. Theprice will reach the level of USD 6.47 per kg. In the future, pricing can be expected by factorssuch as surges in demand or low growth rates. In this case, the price of ferrotitanium may be ator close to 3.0 per kg. Some demand factors are analyzed. The real price of ferrotitanium isexpected to remain low for the foreseeable future.